Drosophila huntingtin-interacting protein 14 is a presynaptic protein required for photoreceptor synaptic transmission and expression of the palmitoylated proteins synaptosome-associated protein 25 and cysteine string protein. - Stowers, R.S.; Isacoff, E.Y. (Journal of Neuroscience, 2007)
Palmitoylation affects the trafficking, stability, aggregation, and/or functional activity of a substantial number of neuronal proteins. We identified mutations in dHIP14, the Drosophila homolog of the human palmitoyl transferase, Huntingtin-interacting protein 14 (HIP14). HIP14 was previously reported to localize primarily to Golgi and to palmitoylate the neuronal proteins synaptosome-associated protein 25 (SNAP-25), PSD-95 (postsynaptic density-95), GAD65, Synaptotagmin, and Huntingtin in mammalian neurons. We find dHIP14 to be an essential maternal effect gene required for photoreceptor synaptic transmission and for proper in vivo expression of the palmitoylated presynaptic proteins SNAP-25 and cysteine string protein. In non-neuronal cells in the fly, dHIP14 protein is found in Golgi. However, in fly neurons, we find dHIP14 primarily in presynaptic terminals, something we also observe with HIP14. In mammalian neurons, we also find a significant fraction of HIP14 colocalizing with a synaptic vesicle marker. Based on localization of the palmitoyl transferase HIP14 within the presynaptic nerve terminal, we propose palmitoylation as a possible mechanism that may be operating to rapidly regulate synaptic efficacy.